2015
DOI: 10.1007/s10464-015-9737-8
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Sustainability of an Evidence‐Based Mental Health Promotion Program in Canadian Elementary Schools

Abstract: Substantial research illuminates many factors effecting the implementation of evidence-based mental health promotion programs in schools; however, research on how schools plan for sustaining their investments in these programs is limited. In this qualitative study, we elicited descriptions of opportunities and challenges for sustainability. We interviewed 24 individuals from schools involved in a longitudinal, qualitative research project that followed uptake and implementation of the evidence-based WITS Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…For school-based programs, inadequate staffing and administrative support hindered sustainment. This finding is consistent with recent studies that suggest that administrative support, consistent resources, and staff stability and buy-in are particularly important in the school context (70,84,90,146).…”
Section: Community Settingssupporting
confidence: 92%
See 2 more Smart Citations
“…For school-based programs, inadequate staffing and administrative support hindered sustainment. This finding is consistent with recent studies that suggest that administrative support, consistent resources, and staff stability and buy-in are particularly important in the school context (70,84,90,146).…”
Section: Community Settingssupporting
confidence: 92%
“…For school-based programs, inadequate staffing and administrative support hindered sustainment. This finding is consistent with recent studies that suggest that administrative support, consistent resources, and staff stability and buy-in are particularly important in the school context (70,84,90,146).Several studies have focused on the sustainability of coalitions aimed at implementing EBIs, including the Communities That Care (CTC) coalition-based prevention system (51) and the PROSPER community-university partnership model (56). A study of 110 CTC sites in Pennsylvania found that 90% of coalitions continued after the three-year initial funding period, with 3-8% of sites terminating each year after (36).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In addition, this study focuses on relatively short‐term effects for cohorts of children in grades one to six followed across two academic years. Sustaining program implementation over time is challenging for both program and school staff (Leadbeater, Gladstone & Sukhawathanakul, ) and the lasting effects of the WITS Programs beyond grade six have not been investigated (Hoglund, Hosan & Leadbeater, ).…”
Section: Discussionmentioning
confidence: 99%
“…At this level, the weight of administrative and organizational demands, such as large class sizes, mandated curricula, instructional strategies, high‐stakes testing that constrains their autonomy, and the implementation of other whole‐school requirements, take their toll on teachers (Moriarty, Edmonds, Blatchford, & Martin, ; Roeser et al, ). In addition to these demands, numerous educational researchers cite stress associated with managing student misbehavior and maintaining discipline, as a major and chronic source of their stress (Bierman et al, ; Leadbeater, Gladstone, & Sukhawathanakul, ). More specifically, when teachers experience negative interactions with difficult students on a daily basis, this interaction pattern becomes a source of negative thoughts and emotions, which can in turn impact teachers’ cognitive functioning and motivation (Emmer & Stough, ; Ouellette et al, ).…”
Section: Introductionmentioning
confidence: 99%